Integrating law and ethics through scenario-based learning in midwifery education: effects on moral sensitivity and reasoning - Suhashini; Suganthi, S.; Vuyyuru, Pratima; Kalaivani, L.; Abirami, M.; Patel, Mayuri; T., Beaulah Mercy Mary; Umar, Mohammed; R., Yashodamma; Katiyar, Jyoti; Chavadannavar, M. P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
This scoping review examined the impact of integrating law and ethics through scenario-based learning (SBL) on moral sensitivity and moral reasoning in midwifery and related health-professional education. Midwives frequently navigate ethically complex and legally consequential decisions in maternity care, making ethical competence essential for safe and respectful practice. However, traditional didactic instruction often fails to prepare students for real-world ethical dilemmas. Using the Arksey and O’Malley framework and PRISMA-SR guidelines, seven major databases were searched from 2000 to 2025, yielding 35 eligible studies. These included midwifery, nursing, medical, and interprofessional education contexts. Findings showed that SBL delivered through written scenarios, high-fidelity simulation, standardized patients, virtual platforms, and problem-based learning consistently enhanced learners’ ability to identify ethical issues, understand legal obligations, and engage in principled moral reasoning. Interventions that incorporated structured debriefing, reflective dialogue, and explicit legal analysis produced the strongest improvements. Moral sensitivity improved in 26 of 31 studies measuring this outcome, particularly when scenarios reflected emotionally charged maternity care situations. Moral reasoning also improved across 18 of 24 studies, with the greatest gains observed when SBL was longitudinal and interactive. Barriers included limited faculty expertise, insufficient legal integration, and resource constraints. Overall, evidence demonstrates that SBL is a powerful pedagogical approach for strengthening ethical and legal competence in midwifery education. The review highlights the need for more midwifery-specific research, culturally adapted scenarios, and rigorous long-term evaluations.